Determinan Kejadian Berat Badan di Bawah Garis Merah (BGM) pada Balita : Determinants of Under-Red Line Weight Occurrence in Toddlers - Rusmilawaty, Rusmilawaty; Tunggal, Tri; Daiyah, Isrowiyatun (Jurnal Bidan Cerdas, 2020)
The prevalence of under-five children under-red line in the working area of Karang Intan I Public Health Center is very high and continues to increase. In 2016 it was 10.3%, and in 2017 it was 12.2%. This study aimed to determine the factors associated with the occurrence of body weight below the red line in toddlers in the working area of Karang Intan 1. This study used analytic survey methods with cross-sectional approach. This study population was all toddlers, amounting to 801 people and a sample of 267 people with the purposive sampling method. The instrument used a questionnaire. The test used was the Chi-Square statistical test. The results showed a relationship between the history of exclusive breastfeeding (Ï=0.001), feeding patterns (Ï=0,000), history of infectious diseases (Ï=0.042), maternal visits to Integrated healthcare center (Posyandu) (Ï=0.002), family economic status (Ï =0,0151) with the occurrence of body weight below the red line (BGM) in infants. Conclusion: there is a relationship between exclusive breastfeeding, eating care, history of infectious diseases, maternal visits to the Posyandu, family economic status towards the occurrence of body weight below the red line in toddlers. Parenting is a significant determinant of BGM events. These determinants can be used for screening the development and growth of infants.